Geographical Distribution of Natural Tourism Areas and Their Statistical Analyzes in Salah al-Din overnorate - Abdullah, Safaa Mahmoud; Taha, Dhafir Ibrahim (Journal of Tikrit University for Humanities, 2024)
Today, tourism is one of the most growing industries in the world, and natural potential is one of the most important tourist attractions, which is known as natural tourism. Hence, the importance of studying the geographical distribution of natural tourism areas and their statistical analyzes in Salah al-Din Governorate, and these areas are represented by river islands, lakes and rivers (Water sports), wild hunting and fishing, exploring high areas, setting up desert camps, natural plants. Through data analysis, it was found that riverine islands are among the most preferred other natural areas in exploiting them for recreational and tourism purposes, due to the availability of many natural ingredients in riverine islands, including water resources and tourism activities such as water sports and fishing, as well as the density of natural vegetation on riverine islands. And all other natural tourism areas are suitable for practicing tourism activities related to them.